Relationship between PROP (6-n-propylthiouracil) taster status and alcoholism, food preference and consumption of young Filipino adult drinkers and nondrinkers - Salomon, Raphael Luis C.; Villarino, Casiana Blanca J. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
The objective of the study was to assess the relationship between PROP taster status and alcoholism, food preference, and consumption of young Filipino adult drinkers and nondrinkers. The food preference and consumption of the selected respondents (n=103) were determined using a self-administered food preference checklist and 3-day food record, respectively. Participants were classified into their drinker status using the alcohol use disorder identification test (AUDIT). PROP taster status was determined based on the participants' intensity perception of 6-n-propylthiouracil and NaCl solutions using a labeled magnitude scale (LMS). The respondents comprised mainly of females (60%) equally divided into drinkers (n=51) and nondrinkers (n=52), and 6% were nontasters, 42% were medium tasters, and 42% were supertasters. No significant correlation (p>0.05) was found between PROP taster status and alcoholism or drinker status. On the other hand, significant correlations (p<0.05) were found between PROP taster status and the preferences for both squash and honey. Supertasters had a significantly higher preference (p<0.05) for squash, while nontasters had a significantly (p<0.05) higher preference for honey. Significant correlations (p<0.05) were found between drinker status and preferences for beverages, foods under the bitter modality, and selected food items (i.e., hotdogs, water spinach, Chinese cabbage, boiled eggs, and mussels). In addition, correlations (p<0.05) were found between PROP taster status, and both protein and niacin intake. A significant correlation (p<0.05) was also found between drinker status and thiamin intake, with drinkers having a significantly lower thiamin intake. Findings of the study imply that PROP and drinker status of young Filipino adults may impact food consumption and preferences.
Thesis Classification: P
Thesis
Includes bibliographical references and appendices.
Keywords: Drinking of alcoholic beverages -- Young adults -- Philippines; Taste